Implementasi Ekopedagogi Dalam Pembelajaran Sekolah Dasar : Meningkatkan Kesadaran Lingkungan Dan Keterlibatan Siswa - Isna Aulia Adzani; Kharisma Nurul Azizah; Nur Joan Adiwinata; Wulan Marthania (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to find out how ecopedagogy is implemented in elementary school learning to increase environmental awareness and student involvement. This article was prepared using the systematic literature review (SLR) method. Searches were carried out using Google Schooler. In the initial stage of the journal search, 235 journal articles were obtained with a time limit, namely from 2014 to 2023. The procedure for searching and selecting articles in this study used preferred reporting items for systematic reviews & meta-analyses (PRISMA). Ecopedagogy discusses three main areas, namely technical ecoliteracy , critical ecoliteracy, and cultural ecoliteracy. The implementation of ecopedagogical integration in elementary school management which aims to instill environmental character values ​​from generation to generation can be carried out in several forms, namely integration in the curriculum and learning by including an understanding of ecology in the subjects or materials taught and the application of methods or media. Environmentally caring character education aims to instill values ​​and awareness of the environment in students. Case studies of the application of ecopedagogy in education show that it can be applied through digital media and multi-dominant learning to develop cognitive, psychomotor and environmental awareness. Barriers to implementing environmentally caring character education in schools include internal factors such as students' bad habits and lack of knowledge, as well as external factors such as inadequate learning support equipment and lack of cooperation between teachers and parents. Collaboration between teachers, students, parents, and the community is essential for successful implementation.